Why Is Implementation Science Important for Intervention Design and Evaluation Within Educational Settings? - Moir, Taryn (Frontiers in Education, 2018)
The current challenging economic climate demands, more than ever, value for money in service delivery. Every service is required to maximise positive outcomes in the most cost-effective ways. To date, a smorgasbord of interventions have been designed to benefit society. Those worthy of attention have solid foundations in empirical research, offering service providers reassurance that positive outcomes are assured. Many of these programmes lie within the field of education and everyday school practice, yet often even these highly supported programmes yield poor results. Therefore, teachers and school staff cast these valuable materials aside, claiming they are ineffective. The question is why. Why do these interventions, grounded in theory and research, fail to translate into positive outcomes? The answer rests within the study of implementation science. Following a brief definition of key terms and theories, this article will go on to discuss why implementation is not a straightforward process. To do so, this article will draw upon examples of poorly implemented, but evidence-based, school programmes. Having acknowledged how poor implementation affects sustainability, we will then look at the growing amount of frameworks for practice within this field. One such framework, The Core Components Model, (Fixsen, Blase, Naoom, & Wallace, 2009) will be used to facilitate discussion around the processes of successful design and evaluation. This article will continue by illustrating how the quality of implementation has directly affected sustainability of The Incredible Years programmes (Webser-Stratton, 2012) and the Promoting Alternative Thinking Strategies (PATHS) curriculum (Greenberg & Kusche, 1996). Then by analysing implementation science, some of the challenges currently faced within this field will be highlighted and areas for further research discussed. This will then link to the implications for educational psychologists (EPs) and will conclude that implementation science is crucial to the design and evaluation of interventions and the EP is in an ideal position to support sustainable positive change.